Obesity and clinical outcomes in COVID-19 patients without comorbidities, a post-hoc analysis from ORCHID trial - Yu, Peng; Tan, Ziqi; Li, Zhangwang; Xu, Yi; Zhang, Jing; Xia, Panpan; Tang, Xiaoyi; Ma, Jianyong; Xu, Minxuan; Liu, Xiao; Shen, Yunfeng (Frontiers in Endocrinology, 2022)
Objective: Large body of studies described individuals with obesity experienced a worse prognosis in COVID-19. However, the effects of obesity on the prognosis of COVID19 in patients without comorbidities have not been studied. Therefore, the current study aimed to provide evidence of the relationship between obesity and clinical outcomes in COVID-19 patients without comorbidities. Methods: A total of 116 hospitalized COVID-19 patients without comorbidities from the ORCHID study (Patients with COVID-19 from the Outcomes Related to COVID-19 Treated with Hydroxychloroquine among Inpatients with Symptomatic Disease) were included. Obesity is defined as BMI ≥30 kg/m2. A Cox regression analysis was used to estimate the hazard ratio (HR) for discharge and death through 28 days. Results: The percentage of obesity in COVID-19 patients without comorbidities was 54.3% (63/116). Discharge at 28 days occurred in 56/63 (84.2%) obese and 51/53 (92.2%) non-obese COVID-19 patients without comorbidities. 28-days death occurred in 4 (3.4%) COVID-19 patients without any comorbidities, among which 2/63 (3.2%) were obese, and 2/53 (3.8%) were non-obese. Multivariate Cox regression analyses showed that obesity was independently associated with a decreased rate of 28-days discharge (adjusted HR: 0.55, 95% CI: 0.35-0.83), but was not significantly associated with 28-days death (adjusted HR: 0.94, 95% CI: 0.18-7.06) in COVID-19 patients without any comorbidities. Conclusions: Obesity was independently linked to prolonged hospital length of stay in COVID-19 without any comorbidities. Larger prospective trials are needed to assess the role of obesity on COVID-19 related death.